Citra Merek Terhadap Minat Beli Konsumen Kopi Kekinian di Jakarta - Tipri Rose; Fifi Nofiyanti (Neolectura, 2020)
Millennial era trend known as contemporary coffee. The South Jakarta region in particular is known for Kenangan Coffe and Fore Coffe. Both of these coffees are one of the coffee shops that are popular with young people today. This study aims to determine the brand image of buying interest in contemporary coffee consumers in Jakarta, especially Kenangan Coffe and Fore Coffe. This research method is quantitative by using descriptive correlation method. The sample in this study used 99 respondents. Data analysis methods used are validity test, reliability test, mean / average test, descriptive correlation analysis, simple linear regression test, coefficient of determination test, and hypothesis testing. The results of this study indicate that there is an interest in buying consumers who are very interested with an average value of 4.29 for Kenangan Coffe and 4.06 for Fore Coffee, which means consumers are already interested and a very well-known brand image for Pondok Indah Mall Kenangan Coffe while Fore Coffee Bintaro Health has known brand image with an average value of 4.26 for Coffee Memories and 3.94 for Fore Coffee. Consumer buying interest has a moderate relationship with brand image in Pondok Kenangan Coffee Pondok Indah Mall and Fore Coffee Bintaro Health with correlation numbers of 0.518 and 0.502 where there is an influence of brand image on consumer buying interest of 26.8% and 25.2%. Based on the results of a simple linear regression test, if the influence of brand image has increased by one unit, then consumer buying interest will increase by 0.401 times for Memories Coffee while Fore Coffee is 0.419 times. And based on the results of the t test in this study showed a significant value. 0,000 <0.05, which means that brand image has a significant effect on consumer buying interest in the Kenangan Coffee Pondok Indah Mall and Fore Coffee Bintaro Health. In this study the influence of a superior brand image and consumer buying interest is Kenangan Coffee.